The approach to fracture diagnosis by means of experimental measurements of the stored energy - Alena Vedernikova; A. Iziumova; A. Vshivkov; Oleg Plekhov (Fracture and Structural Integrity)
The energy dissipation in metals in the process of irreversible deformation leads to intensive heat generation in the areas in the strain localization zones. This work is devoted to the measuring the power of heat sources by means of the data of temperature generated using IR thermography. Verification of calculated values of power of heat sources is carried out by the use of heat flux sensor that based on the Seebeck effect. The quasi-static experimental studies on the tensile were conducted on the flat titanium alloy Grade 2 specimens. A good agreement between the thermography and the measured directly using heat flux sensors was shown. The measurements showed the relationship between the moment of fracture of metal specimens and the change in the nature of localized heat generation caused by irreversible deformation.